2016
DOI: 10.1104/pp.15.01309
|View full text |Cite
|
Sign up to set email alerts
|

TEMPRANILLO Reveals the Mesophyll as Crucial for Epidermal Trichome Formation

Abstract: Plant trichomes are defensive specialized epidermal cells. In all accepted models, the epidermis is the layer involved in trichome formation, a process controlled by gibberellins (GAs) in Arabidopsis rosette leaves. Indeed, GA activates a genetic cascade in the epidermis for trichome initiation. Here we report that TEMPRANILLO (TEM) genes negatively control trichome initiation not only from the epidermis but also from the leaf layer underneath the epidermis, the mesophyll. Plants over-expressing or reducing TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 71 publications
4
45
0
Order By: Relevance
“…Under this condition, 35S::TEM1 plants also showed a substantially long juvenile phase, an unexpectedly short adult phase (Figures i,j and S1k,l, Table S2i,j) and flowered later than the wild‐type (Figures i,j and S2k,l, Table S3i,j). Most 35S::TEM1 plants did not produce leaves with abaxial trichomes, probably due to the fact that these plants, in addition to having a late juvenile‐to‐adult transition, produce very few leaf trichomes (Matías‐Hernández et al ., ). Due to the similar results obtained with all genotypes under both photoperiods we therefore used LD conditions for all subsequent experiments.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Under this condition, 35S::TEM1 plants also showed a substantially long juvenile phase, an unexpectedly short adult phase (Figures i,j and S1k,l, Table S2i,j) and flowered later than the wild‐type (Figures i,j and S2k,l, Table S3i,j). Most 35S::TEM1 plants did not produce leaves with abaxial trichomes, probably due to the fact that these plants, in addition to having a late juvenile‐to‐adult transition, produce very few leaf trichomes (Matías‐Hernández et al ., ). Due to the similar results obtained with all genotypes under both photoperiods we therefore used LD conditions for all subsequent experiments.…”
Section: Resultsmentioning
confidence: 97%
“…Unexpectedly, when TEM1 is overexpressed, instead of an extension of the adult phase we observed a dramatic lengthening of the juvenile phase under both LDs and SDs, together with an extreme shortening or even suppression of the adult phase under LDs (Figure 1i,j). However, 35S:: TEM1 plants show a dramatically reduced trichome density (Mat ıas-Hern andez et al, 2016). Therefore, it is possible that the alteration of the number of leaves without and with abaxial trichomes in these plants is a combination of the effects on the juvenile-to-adult transition and on trichome density.…”
Section: The Regulation Of Flowering By Tems Is Partially Mediated Bymentioning
confidence: 99%
“…), while AtTEM2 represses trichome formation (Matias‐Hernandez et al . ), and the loss of AtCML42 expression results in trichomes with abnormal structures and increased branching (Dobney et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…In this issue, Matías-Hernández et al (2016) reported that two transcription factors, TEMPRANILLO1 (TEM1) and TEM2, inhibit trichome initiation from the underneath layer of the epidermis, the mesophyll. Matías-Hernández et al (2016) found that TEM genes expressed in the mesophyll cells can still affect epidermal trichome formation, suggesting the existence of a non-cell-autonomous regulation. Surprisingly, bioactive fluorescently labeled GA 3 , which was applied on top of leaves, accumulated exclusively in the mesophyll cells, but not in the epidermis, suggesting that the distribution of GA is under active regulation.…”
mentioning
confidence: 99%
“…Indeed, TEMs suppress the expression of these newly identified GA transporters, and also suppress GA biosynthesis, to regulate GA distribution (Matías-Hernández et al, 2016). In fact, TEMs can reduce the mesophyll-specific accumulation of fluorescently labeled GA 3 .…”
mentioning
confidence: 99%